Pengaruh Electronic Word Of Mouth Dan Promosi Media Sosial Terhadap Minat Beli Pada Produk Fashion Eiger - Bona Aripin Sinaga; Sulistiono Sulistiono (LPPM Institut Bisnis dan Informatika Kesatuan, 2020)
Eiger as a fashion brand and outdoor equipment often promotes social media through advertisements on social media, but the advertisement is sometimes not well targeted, so it is seen by many people who do not like to do outdoor activities, which makes the promotion by Eiger ineffective. This study aims to 1). Knowing the effect of eWOM on buying interest in Eiger fashion products in Bogor, 2). Knowing the effect of promoting social media on buying interest in Eiger fashion products in Bogor, and 3). To determine the effect of electronic word of mouth and social media promotion on buying interest in Eiger fashion products in the city of Bogor. This research uses a quantitative approach involving 100 respondents. Primary data collection using a questionnaire and secondary data collection using literature study. Hypothesis testing in this study uses multiple linear regression analysis with a significance value  = 5% using SPSS 22 analysis tools. The results of the study show that simultaneously electronic variable word of mouth and social media promotion variables have positive and significant influence on buying interest. Partially the electronic word of mouth variable has a positive and significant influence on buying interest, as well as the variable of social media promotion which has a significant and positive influence on buying interest. Keywords: electronic word of mouth, buying interest, social media promotion